The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1982
DOI: 10.1104/pp.70.6.1619
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Variation of Four Cytokinins in Soybean Root Pressure Exudate

Abstract: No correlation was found between cytokinin fluxes and nodule dry weight or specific nodule activity (acetylene reduction).The timing of distinct peaks in zeatin riboside and dihydrozeatin riboside fluxes during flowering or pod formation suggests that cytokinins exported from the root may function in the regulation of reproductive growth in soybean.The roles of cytokinins in plant growth and development are not fully understood, but evidence supports the hypothesis that cytokinins are produced by the root syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
42
2
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 14 publications
6
42
2
1
Order By: Relevance
“…Such a phenomenon, i.e. a low cytokinin content in exudate at the early reproductive stage, has been observed in rice (23) and soybean (8). After heading, the cytokinin activities declined as leaves senesced and grains filled.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Such a phenomenon, i.e. a low cytokinin content in exudate at the early reproductive stage, has been observed in rice (23) and soybean (8). After heading, the cytokinin activities declined as leaves senesced and grains filled.…”
Section: Discussionmentioning
confidence: 91%
“…As such, the exudation rate and cytokinin biosynthesis in the root may be controlled by different systems. In fact, lack of similarities between exudation rate and cytokinin flux has been shown in tomato (3), lupine (4,5), sunflower (18), and soybean (8). Hence, we presented our results as amount of cytokinin per plant per 12 h and not as concentration.…”
Section: Discussionmentioning
confidence: 97%
“…Liu et al (2003) found that the reduced pod-set percentage induced by water defi cit was associated with an increase in ABA content of reproductive structures during a period from 3 to 5 days after anthesis. Endogenous cytokinins detected in exudate showed a maximum concentration during a period from 0 to 9 days after anthesis, when most fl owers are destined to either initiate or abort pods (Heindl et al, 1982;. The application of BA to racemes reduced abortion and increased pod number (Crosby et al, 1981;Carlson et al, 1987;Dyer et al, 1987;Peterson et al, 1990;Mosjidis et al, 1993;Reese et al, 1995;Nagel et al, 2001).…”
mentioning
confidence: 96%
“…By reducing this abortion, we might be able to increase pod and seed numbers, thereby increasing the yield (Kokubun, 2004). Many previous studies have focused on two possible factors that might be involved in regulating the abortion; availability of photoassimilate or nutrients (Brevedan et al, 1978;Antos and Wiebold, 1984;Brun and Betts, 1984;Heitholt, 1986aHeitholt, , 1986b and quantity of certain hormones (Huff and Dybing, 1980;Heindl et al, 1982;Spollen et al, 1986aSpollen et al, , 1986bCarlson et al, 1987;Yarrow et al, 1988;Kokubun and Honda, 2000).…”
mentioning
confidence: 99%
“…They concluded the developing seeds do not accumulate significant proportions of these cytokinins. The principal xylem cytokinins in soybean appear to be ZR and DZR (8). Since the latter is more stable than ZR (12), it is particularly important to assess its translocation pattern and metabolism using the explant system.…”
mentioning
confidence: 99%